Meningkatkan Produktivitas Olahan Dari Jagung Pulut Pada Masyarakat Di Desa Buhu Kecamatan Tibawa Kabupaten Gorontalo - Syahdiya, Halimathus; Abdul, Nurjana; Djafar, Mutiara Febrianti Y.; Samadi, Devrianti; Isa, Liya; Pakaya, Mohamad Ikbal (Universitas Negeri Gorontalo, 2023)
AbstractCorn is one of the superior commodities compared to other food commodities. In Indonesia, corn as a food ingredient is the second source of carbohydrates after rice. Corn besides being a source of calories, also supplies nutrients to obtain a nutritional balance of the population. Buhu Village has natural potential in the form of corn including pulut corn. For agricultural products on corn sticky rice, most of the people in Buhu village only depend on the selling value of sticky corn in wet and dry form, there is no processing of sticky corn in the form of a new product. Therefore the purpose of this activity is to assist the community in increasing the productivity of the processed corn pulp itself. This training took place in the hall of the Buhu village office by involving some of the community, farmer group leaders, and village officials, in its implementation using the Model Community Development approach, namely an approach that directly involves the community as the subject and object of carrying out counseling and training activities. The hope that was achieved in these activities was that the Buhu village community was more creative in making processed pulut corn so that it would attract a lot of consumer interest.Keywords: Productivity, Pulut Corn, Marketing